Gross anatomical study on the liver of the one humped camel (Camelus dromedarius) (Journal of Veterinary Medicine and Animal Production, 2022)
ct Thirty five livers of adult dromedary camels were grossly examined. The topography of the liver and the extrahepatic blood supply were studied in two foetuses (third trimester). The intrahepatic portal blood supply was studied in a liver injected with 12% Vinylite through the portal vein. The dromedary liver appeared characteristically as an enlarged irregular prism, and had a very high content of interlobular connective tissues, which lent a firmer consistency to the liver, acharacteristic which was not found in the liver of any other domestic mammal. In the foetus, the liver protruded beyond the thoracic cage on the right and left sides of the abdominal cavity, but the bulk was on the right side. The liver of the adult camel looked dark brown in colour. It weighed about 7.5 kgs, measured 67 cm in length and 48 cm in width. The dromedary liver showed four distinct lobes namely; left )lateral and medial(, right, caudate, and quadrate. The liver was supplied by the hepatic artery, and by the portal vein which terminated at the porta by dividing into three branches; right dorsal, right ventral, and a much larger left branch. The liver was drained by many hepatic veins. These veins are of three categories, two large, six to eight medium, and thirty four to thirty eight small one